FMI: Fault Tolerant Messaging Interface for Fast and Transparent Recovery - Sato, Kento; Moody, Adam; Mohror, Kathryn; Gamblin, Todd; de Supinski, Bronis R.; Maruyama, Naoya; Matsuoka, Satoshi (Proceedings - IEEE International Parallel and Distributed Processing Symposium, 2014)
Future supercomputers built with more components will enable larger, higher-fidelity simulations, but at the cost of higher failure rates. Traditional approaches to mitigating failures, such as checkpoint/restart (C/R) to a parallel file system incur large overheads. On future, extreme-scale systems, it is unlikely that traditional C/R will recover a failed application before the next failure occurs. To address this problem, we present the Fault Tolerant Messaging Interface (FMI), which enables extremely low-latency recovery. FMI accomplishes this using a survivable communication runtime coupled with fast, in-memory C/R, and dynamic node allocation. FMI provides message-passing semantics similar to MPI, but applications written using FMI can run through failures. The FMI runtime software handles fault tolerance, including check pointing application state, restarting failed processes, and allocating additional nodes when needed. Our tests show that FMI runs with similar failure-free performance as MPI, but FMI incurs only a 28% overhead with a very high mean time between failures of 1 minute.